ANALISIS KETIMPANGAN PEMBANGUNAN REGIONAL DI DAERAH PROVINSI SUMATERA UTARA (Jurnal Ekonomi Bisnis dan Akuntansi, 2022)
Sustainable economic development in the province of North Sumatra has provided economic and social improvements for the community. On the other hand, several economic constraints that arise between regions, both human resources and capital resources, have created inequality in achievement between districts/cities. This study aims to determine and analyze the effect of investment and balancing funds that enter the region, as well as the labor force and agglomeration in the area to reduce inequality between districts or cities in the province of North Sumatra. This empirical research method uses multiple linear regression analysis with a qualitative approach. The results of this study indicate that economic growth in the Sumatran region has varying levels of diversity, this is because each province has different potential in terms of both natural resources and human resources and the quality of the technology possessed by the province. Differences in the level of development will have an impact on differences in the level of welfare between regions, which in turn will cause regional disparities between regions to increase.